2017
DOI: 10.4111/icu.2017.58.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Predicting biochemical recurrence in patients with high-risk prostate cancer using the apparent diffusion coefficient of magnetic resonance imaging

Abstract: PurposeWe aimed to investigate whether the apparent diffusion coefficient (ADC) value in diffusion-weighted magnetic resonance imaging predicts the prognoses of patients with high-risk prostate cancer.Materials and MethodsA total of 157 patients with high-risk prostate cancer (based on D'Amico's criteria) were included in the analysis. Patients underwent preoperative 3.0 Tesla magnetic resonance imaging within 2 months before radical prostatectomy. Those who received neoadjuvant hormone therapy (33 persons) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…Recently, Kim et al (2) reported a mean ADC value for disease with a GS of 7 equal to 0.741±0.164×10 -3 mm 2 /s; moreover, Salami et al (16) showed that larger prostate cancers were associated with lower ADC values. Finally, Yoon et al (17) and Kido et al (18) demonstrated that ADC was significantly associated with biochemical-free recurrence and extracapsular PCa extension, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kim et al (2) reported a mean ADC value for disease with a GS of 7 equal to 0.741±0.164×10 -3 mm 2 /s; moreover, Salami et al (16) showed that larger prostate cancers were associated with lower ADC values. Finally, Yoon et al (17) and Kido et al (18) demonstrated that ADC was significantly associated with biochemical-free recurrence and extracapsular PCa extension, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], clinical stage T1c and median GS equal to 6.8 (range=6-9) underwent radical retropubic prostatectomy (RRP) for biopsy of clinically significant PCa (GS ≥6 and/or more than 2 positive cores and/or a greatest percentage of cancer for each core >50%) (10); 16/44 (36.6%) patients previously enrolled in Active Surveillance (AS) program were upgraded at confirmatory biopsy and 28/44 (63.4%) men underwent repeat saturation biopsy (median=30 cores; range=28-34 cores) for persistent suspicious cancer. Previously, all patients about 10 days before prostate biopsy underwent pelvic mpMRI and two radiologists blinded to pre-imaging clinical parameters evaluated the mpMRI data separately and independently.…”
Section: Methodsmentioning
confidence: 99%
“…(iv) Differences between scanners and imaging techniques will probably result in slightly different cut-off points, presumably in a similar range around 650, 800 and 950 mm 2 /s. However, Yoon et al [ 19 ] dichotomised at the ADC level of 746 mm 2 /s. The differences in ADC cut-off from our study were most probably due to differences in scanner, b values and their high-risk patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, multiparametric MRI (mpMRI) of the prostate was introduced for detection and localisation of PCa. Recent studies indicate that mpMRI has a high diagnostic accuracy for detection of PCa [ 12 , 13 ], can improve predictions of preoperative clinical nomograms, at least for locally advanced disease [ 14 , 15 ], and that mpMRI may both improve predictions of clinical BCR nomograms [ 16 19 ] and improve risk stratification for detection of significant PCa [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A change in tumour cellularity, perfusion and cellular necrosis following treatment is reflected in a change in the ADC value, and the potential utility of DWI in tumour detection, grading and assessment of treatment response has been demonstrated in a range of tumour types. 39 , 40 ADC values have been assessed in patients with HNSCC treated with chemoradiation. Significantly lower pre-treatment ADC values were found in complete responders when compared to partial responders, suggesting that this biomarker could be used to predict response to treatment and may even allow for dose-modification.…”
Section: Advances In Mrimentioning
confidence: 99%